CHH methylation of genes associated with fatty acid and jasmonate biosynthesis contributes to cold tolerance in autotetraploids of Poncirus trifoliata. Issue 12 (22nd November 2022) - Wang, Yue; Zuo, Lanlan; Wei, Tonglu; Zhang, Yu; Zhang, Yang; Ming, Ruhong; Bachar, Dahro; Xiao, Wei; Madiha, Khan; Chen, Chuanwu; Fan, Qijun; Li, Chunlong; et al.
Abstract: Polyploids have elevated stress tolerance, but the underlying mechanisms remain largely elusive. In this study, we showed that naturally occurring tetraploid plants of trifoliate orange ( Poncirus trifoliata (L.) Raf.) exhibited enhanced cold tolerance relative to their diploid progenitors. Transcriptome analysis revealed that whole‐genome duplication was associated with higher expression levels of a range of well‐characterized cold stress‐responsive genes. Global DNA methylation profiling demonstrated that the tetraploids underwent more extensive DNA demethylation in comparison with the diploids under cold stress. CHH methylation in the promoters was associated with up‐regulation of related genes, whereas CG, CHG, and CHH methylation in the 3'‐regions was relevant to gene down‐regulation. Of note, genes involved in unsaturated fatty acids (UFAs) and jasmonate (JA) biosynthesis in the tetraploids displayed different CHH methylation in the gene flanking regions and were prominently up‐regulated, consistent with greater accumulation of UFAs and JA when exposed to the cold stress. Collectively, our findings explored the difference in cold stress response between diploids and tetraploids at both transcriptional and epigenetic levels, and gained new insight into the molecular mechanisms underlying enhanced cold tolerance of the tetraploid. These results contribute to uncovering a novel regulatory role of DNA methylation in better cold tolerance of polyploids. Abstract : The autotetraploids of trifoliate orange ( Poncirus trifoliata ), a widely used rootstock for citrus, show enhanced cold tolerance, which can be ascribed to extensive alterations of the global transcriptome and methylome of stress‐responsive genes involved in a range of metabolic pathways, including unsaturated fatty acids and jasmonate metabolism.